Italian Polyptychs from Late Duecento to Early Quattrocento Changing Contexts: From Cult Objects to the Museum Exhibits - Nazarova, Olga A. (Actual Problems of Theory and History of Art, 2017)
This article studies the history of existence, viewing and studying of the Early Italian panelpaintings (mostly polyptychs of Trecento and Early Quattrocento) during the period from the 15th to the 21st centuries. Based on several keyexamples like Maesta by Duccio di Buoninsegna, Sassetta’s altarpiece from the Church of San Francesco in Borgo San Sepolcro, and others, the article presents this history as a one proceeding from the creative dialogue with the early polyptychs in the Late Quattrocento painting towards the continual loss by the early polyptychs of their original status, function and, spatial context due to the Counter-Reformation church interiors transformations in the second half of the 16th century. In the later centuries many panels lost even their physical entity and original appearance, being dismembered and sold out as objects of collecting and/or museum exhibits. This history is inevitably a history of losses, sometimes fatal, but simultaneously this is also a history of gaining. During the course of these centuries, the painted panels have gained new status and new values, new viewers and new devotees as objects of art and masterpieces of painting. And after being reevaluated as something totally different from what they had been originally, the painted panels ended up as objects of research. Thus, this reevaluation became the basic premise of the scientific recovering (wherever possible) of what has been lost: the original appearance and spatial collocation, patrons’ concernsand first viewers’ attitudes.
Keywords: Italian polyptych; altarpiece; Italian panel painting; Trecento painting; Quattrocento painting; history of collecting; Italian primitives; polyptych reconstruction